Utilization of Cow Manure Using Biogas Technology to Produce Fuel for the Community in Pucak Village, Tompobulu District, Maros Regency - Hamri; Mardin Husen; Amrullah (Best Journal of Administration and Management, 2023)
The conditions in Pucak Village, Tompobulu District, Maros Regency illustrate the enormous regional potential for managing natural resources in the era of regional autonomy, where the Diffusion and Utilization of Science and Technology Programs in remote villages have not been optimally studied. The desired impact of this program is the use of natural resources in the village to become an alternative energy source, namely renewable energy through the production of biogas from cow dung.The service is aimed at providing knowledge to residents about the use of new and renewable energy sources, namely energy produced with appropriate technology that is relatively simple and suitable for rural areas. Biogas processing provides many benefits for residents in managing livestock manure into biogas energy as an alternative fuel that is environmentally friendly, where processing livestock waste into biogas can reduce environmental pollution, where waste is managed into alternative fuels, where the results of waste management have disposal which is then reprocessed into solid or liquid organic fertilizer.